Primary marginal zone B-cell lymphoma of appendix - Radha S; Afroz Tameem; Satyanarayana G (Wolters Kluwer Medknow Publications, 2008)
Primary lymphomas of appendix are extremely rare tumors. The first case of primary lymphoma of appendix was reported by Warren in the year 1898. Incidence of primary lymphoma of appendix is 0.015% of all gastrointestinal lymphomas. This is a report of primary marginal zone B-cell lymphoma of appendix which presented as appendicular mass. As some cases are incidentally discovered, this case emphasizes that histological examination of all appendicectomy specimens is mandatory.